Предмет: Алгебра, автор: maily08ry

Упростить
1)1+sin(-a)/cos(-a) - tg(-a)=
2) cos^2(-a)-cos^4(-a)/sin^2(-a) =
a-альфа
Заранее спасибо

Ответы

Автор ответа: ipsumav
0
1) = frac{1-sin alpha }{cos alpha }-(-tg alpha )= frac{1}{cos alpha }- frac{sin alpha }{cos alpha }+tg alpha =frac{1}{cos alpha }-tg alpha +tg alpha =frac{1}{cos alpha }
2)= frac{cos^2 alpha *(1-cos^2 alpha )}{-sin^2 alpha }= frac{cos^2 alpha* sin^2 alpha }{-sin^2 alpha }=-frac{cos^2 alpha* sin^2 alpha }{sin^2 alpha }=-cos^2 alpha  

Похожие вопросы
Предмет: Математика, автор: vovkastream
Предмет: Математика, автор: zalinamamedova82
Предмет: Информатика, автор: Анна63452